PENGARUH HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI SPBU 7593741 DI KOTA BAUBAU - Hasni (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to examine the effect of price and location on consumer purchasing decisions at SPBU 7593741 in Baubau City. The research employed a quantitative approach with a sample of 80 consumers selected using the Slovin formula. Data were collected through structured questionnaires and analyzed using multiple linear regression analysis. The findings reveal that price does not have a significant effect on purchasing decisions, as fuel prices are standardized and regulated by the government. Conversely, location demonstrates a positive and significant influence on consumer behavior, indicating that strategic positioning and accessibility are critical factors in attracting customers. Simultaneously, both variables significantly affect purchasing decisions, with a coefficient of determination of 40.2%, suggesting that other factors also contribute to consumer choices. These results emphasize the importance of location optimization in enhancing competitive advantage within the fuel retail industry.